2015
DOI: 10.1038/onc.2015.397
|View full text |Cite|
|
Sign up to set email alerts
|

Cytosolic PKM2 stabilizes mutant EGFR protein expression through regulating HSP90–EGFR association

Abstract: Secondary mutation of epidermal growth factor receptor (EGFR) resulting in drug resistance is one of the most critical issues in lung cancer therapy. Several drugs are being developed to overcome EGFR tyrosine kinase inhibitor (TKI) resistance. Here, we report that pyruvate kinase M2 (PKM2) stabilized mutant EGFR protein by direct interaction and sustained cell survival signaling in lung cancer cells. PKM2 silencing resulted in markedly reduced mutant EGFR expression in TKI-sensitive or -resistant human lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 50 publications
5
39
0
Order By: Relevance
“…The association between eNOS and PKM2 appeared to be mediated by Hsp90, as both eNOS and Hsp90 could be detected in PKM2 immunoprecipitates from growth factor‐stimulated endothelial cells (Fig F). In line with the fact that PKM2 has been identified as an Hsp90 client protein in other cellular systems (Subbaramaiah et al , ; Yang et al , ), PKM2 and Hsp90 also formed complexes in HEK293 cells in the absence eNOS (Fig EV1B). To determine whether or not the increased association of PKM2 with eNOS was a consequence of the higher eNOS activity, experiments were repeated using a S633D‐eNOS mutant that also displays a higher NO output (Boo et al , ).…”
Section: Resultssupporting
confidence: 73%
“…The association between eNOS and PKM2 appeared to be mediated by Hsp90, as both eNOS and Hsp90 could be detected in PKM2 immunoprecipitates from growth factor‐stimulated endothelial cells (Fig F). In line with the fact that PKM2 has been identified as an Hsp90 client protein in other cellular systems (Subbaramaiah et al , ; Yang et al , ), PKM2 and Hsp90 also formed complexes in HEK293 cells in the absence eNOS (Fig EV1B). To determine whether or not the increased association of PKM2 with eNOS was a consequence of the higher eNOS activity, experiments were repeated using a S633D‐eNOS mutant that also displays a higher NO output (Boo et al , ).…”
Section: Resultssupporting
confidence: 73%
“…picard.ch/downloads/Hsp90interactors.pdf), including EGFR (Ahsan et al, 2012), AKT (Basso et al, 2002), SAPK (Tatebe and Shiozaki, 2003), p38 (Ota et al, 2010), PKC (Gould et al, 2009), FAK (Xiong et al, 2014), and DNA-PK (Solier et al, 2012). Hsp90 controls the maturation and intracellular trafficking of ErbB2family proteins, including EGFR (Xu et al, 2001(Xu et al, , 2002Yang et al, 2016). The biological function of Hsp90 relies on an inherent ATPase activity that is modulated by many of its co-chaperones.…”
Section: Ifits As Putative Co-chaperonesmentioning
confidence: 99%
“…Protein concentration was determined using the BCA Protein Assay Kit (Pierce) according to the manufacturer's instructions. One thousand five hundred milligrams of protein were incubated with indicated antibodies overnight and then mixed with protein A or protein G‐agarose beads …”
Section: Methodsmentioning
confidence: 69%
“…In addition, we established a PKM2 knockdown approach in Y79 cells (Figure D), in which the levels of C‐MET also showed no significant differences (Figure D); however, we found that HGF‐induced Y79 cell proliferation was suppressed by PKM2 knockdown (Figure E). Previous studies have demonstrated that PKM2‐regulated tumourigenesis mainly depends on its nuclear translocation function . Therefore, in western blot analysis of PKM2 in Y79 cells after cytoplasmic nucleus separation, the results showed that HGF promoted nuclear translocation of PKM2, a process that was dependent on C‐MET function (Figure F).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation